Copula Construction in Kathariya Tharu - Paudel, Krishna Prasad; Khanal, Kamal Krishna (Bharatpur Pragya: Journal of Multidisciplinary Studies, 2023)
Kathariya Tharu is one of the least studied Indo-Aryan languages spoken by the Kathariya Tharu community living in Kailali district of Nepal and Gorakhpur, Gonda, Lakhimpur, and Khiri districts of India. This is a preliminary study which analyses the morphosyntactic structure of copula construction in this language. The linguistic data for this study were collected from Ghodaghodi municipality, ward no. 9, Sisaiya, ward no.12, Kota and Kailari rural municipality, ward no. 8, Lausa and were analyzed with the help of the Toolbox software. R. M. W. Dixon’s Basic Linguistic Theory has been employed as analytical tool, though insights have also been taken from other linguists. Kathariya Tharu employs the verbal copula construction strategy with three copula verbs- ho, ba, and rəh. Unlike other NIA languages in which the relation between the copula subject and copula complement is prominent, in Kathariya Tharu, it is the copula subject that determines the selection of the copula verb. However, the person, relation and function distinctions between the copula subject and copula complement disappears in the past tense and so, the same copula rəh is used with all the subjects.